2009
DOI: 10.1099/vir.0.010769-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of citrus hosts on the generation, maintenance and evolutionary fate of genetic variability of citrus exocortis viroid

Abstract: Citrus exocortis viroid (CEVd) populations are composed of closely related haplotypes whose frequencies in the population result from the equilibrium between mutation, selection and genetic drift. The genetic diversity of CEVd populations infecting different citrus hosts was studied by comparing populations recovered from infected trifoliate orange and sour orange seedling trees after 10 years of evolution, with the ancestral population maintained for the same period in the original host, Etrog citron. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 67 publications
0
25
0
3
Order By: Relevance
“…Las plantas fueron cultivadas de forma individual en macetas de plás-tico de 4 L y mantenidas en invernadero con 28-32 °C. Durante año y cuatro meses se registró el desarrollo de síntomas descritos por Roistacher (1991) y Bernard et al (2009), se detectó la presencia de CEVd por RT-PCR y se midió la altura del nivel del suelo hasta el brote más alto.…”
Section: Fully Bilingualunclassified
See 4 more Smart Citations
“…Las plantas fueron cultivadas de forma individual en macetas de plás-tico de 4 L y mantenidas en invernadero con 28-32 °C. Durante año y cuatro meses se registró el desarrollo de síntomas descritos por Roistacher (1991) y Bernard et al (2009), se detectó la presencia de CEVd por RT-PCR y se midió la altura del nivel del suelo hasta el brote más alto.…”
Section: Fully Bilingualunclassified
“…Los resultados de la secuenciación mostraron que los fragmentos obtenidos correspondían al Citrus exocortis viroid con 99 % de similitud y 99 % de cobertura con un tamaño de 310 pb indicando su presencia en las plantas indicadoras. Probablemente el alto valor de similitud encontrado se deba a que la composición genética del viroide suele no variar cuando es inoculado en el mismo tipo de hospedero de donde se aisló originalmente y a que los viroides se componen de haplotipos estrechamente relacionados (Bernard et al, 2009). La detección de viroides en cítricos por RT-PCR es una herramienta útil (Saponari et al, 2013;Papayiannis, 2014) que no representa una desventaja al diagnóstico biológico ya que las aportaciones del indexado están relacionadas con el estudio de la interacción planta patógeno en un ambiente controlado de desarrollo sequencing showed that the fragments obtained corresponded to the Citrus exocortis viroid with a similarity of 99% and 99% coverage with a size of 310 pb, indicating its presence in indicator plants.…”
Section: Fully Bilingualunclassified
See 3 more Smart Citations